Episodic memory retrieval success is associated with rapid replay of episode content - Wimmer, GE; Liu, Y; Vehar, N; Behrens, TEJ; Dolan, RJ (Nature Research, 2020)
Retrieval of everyday experiences is fundamental for informing our future decisions. The fine-grained neurophysiological mechanisms that support such memory retrieval are largely unknown. We studied participants who first experienced, without repetition, unique multicomponent 40-80-s episodes. One day later, they engaged in cued retrieval of these episodes while undergoing magnetoencephalography. By decoding individual episode elements, we found that trial-by-trial successful retrieval was supported by the sequential replay of episode elements, with a temporal compression factor of >60. The direction of replay supporting retrieval, either backward or forward, depended on whether the task goal was to retrieve elements of an episode that followed or preceded, respectively, a retrieval cue. This sequential replay was weaker in very-high-performing participants, in whom instead we found evidence for simultaneous clustered reactivation. Our results demonstrate that memory-mediated decisions are supported by a rapid replay mechanism that can flexibly shift in direction in response to task goals.